TRANSLATION TECHNIQUES OF HUMOR PUNCHES IN "WEREWOLVES WITHIN" MOVIE - Rafaelino Pandu Iswardhana; Dwi Aji Prajoko (Humaniora Scientia, 2022)
A punch line is an unexpected and humorous conclusion to any show, situation, or story. This is the most crucial thing in humor. It must be retained in the translation. Therefore, the choice of translation technique must be more careful. This research was aimed at analyzing the type of translation techniques on each punch line in the Werewolves Within movie. In this research, the researcher applied Molina & Albir’s (2002) theory of translation techniques. This research was classified as descriptive qualitative research. The data collection technique is document analysis, namely by analyzing the movie subtitle entitled The Werewolves Within. The data analysis technique was ethnographic, namely by differentiating the data and non-data, taxonomizing them, analyzing their components, and analyzing their dominant findings. The results showed that ten out of twenty-four types of translation techniques were used in this research. The dominant type of translation technique was established equivalence, and the least one was addition, adaptation, implicitation, concision, particularization, modulation, and compensation. Each of them got one piece of data.Keywords: Translation Technique, Punchline, Subtitle